2016
DOI: 10.1177/0735633116649373
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Quality of Educational Technology Matters

Abstract: In large-scale international assessments such as the Programme for International Student Assessment (PISA), the Trends in International Mathematics and Science Study (TIMSS), or the Progress in International Reading Study (PISA), research has struggled to find positive associations between the frequency of educational technology use in schools and student achievement. While computer use at home showed a tendency for positive correlations with test scores, computer use in schools did not. Following a different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
52
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(75 citation statements)
references
References 37 publications
14
52
0
9
Order By: Relevance
“…These results indicate that students who use ICT resources more often for academically related work, tend to have lower reading scores. These results are in line with the associations found between ICT use at school and reading performance in PISA 2012 (Petko et al 2017). As in 2015, the 2012 data shows that ICT use at school is negatively related to reading achievement.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…These results indicate that students who use ICT resources more often for academically related work, tend to have lower reading scores. These results are in line with the associations found between ICT use at school and reading performance in PISA 2012 (Petko et al 2017). As in 2015, the 2012 data shows that ICT use at school is negatively related to reading achievement.…”
supporting
confidence: 81%
“…A positive relationship with academic achievement was also found when the computer at home was used for education and communication (Fuchs and Wöβmann 2005). Whereas Petko et al (2017) also found that ICT use at home for schoolwork (browsing the internet for schoolwork, using email for communication with other students about schoolwork, and doing homework on a computer) was positively associated with reading achievement, Hu et al (2018) showed a negative association between ICT use at home for schoolwork and reading performance. One reason for the mixed results might be found in the way ICT use at home for schoolwork was measured in both studies.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…In this regard, the school itself is particularly relevant (e.g. Davis et al 2013;Eickelmann et al 2016;Hatlevik et al 2014;Petko et al 2015Petko et al , 2016Tondeur et al 2008).…”
mentioning
confidence: 99%
“…note that student-centred pedagogies specifically designed to use tablet technologies led to a 0.68 effect size. D. Petko, Cantieni, and Prasse (2017) note that many of the variables that influence student performance in Program for International Student Assessment (PISA) testing are not evident to researchers when using effect size. Hence, the ways digital technologies influence student learning may not be adequately elucidated by effect size analysis nor by quantitative measures.…”
Section: Improving Learningmentioning
confidence: 99%